The rationality of sincere software agent in task completion - Jaafar N.H.; Ahmad M.S.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Behavioral research; Multi agent systems; Robotics; Agent society; Human society; Rational agents; Selfish Agents; Sincerity; Task performance; Teamwork; Work environments; Software agents